Complex Lithiation Mechanism of Siloxene and Germanane: Two Promising Battery Electrode Materials. Issue 1 (7th January 2021) - Loaiza, L. C.; Dupré, N.; Davoisne, C.; Madec, L.; Monconduit, L.; Seznec, V.
Abstract : The layered siloxene and germanane, derived from CaSi2 and CaGe2, respectively, have shown very promising results as anodes for Lithium-ion batteries. Their delivered capacities, capacity retention and high rate cycling are superior compared to bulk Si and Ge. These positive features are most probably related to the layered morphology that buffers the volume changes and improves the kinetics. Despite numerous recently published studies regarding their electrochemical properties, very little is known about their electrochemical mechanism. In this work, we have used a combination of different characterization techniques to study the processes taking place during the lithiation of siloxene and germanane and compared with Si and Ge. Our results suggest a slightly different pathway for the lithiation of siloxene and germanane: their initial layered morphology is preserved after cycling, the crystalline Li15 Si4 and Li15 Ge4 characteristic of an alloying mechanism are absent and possibly different lithiated intermediates are formed. We provide then, an initial assessment of the involved Lix Si and Lix Ge phases and propose the hypothesis of a reversible Li intercalation in the siloxene and germanane layers.